Work systems as the core of the design space for organisational design and engineering. (15th September 2010) - Alter, Steven
This paper contributes to the initial development of organisational design and engineering (ODE). It proposes a work system perspective on ODE by showing how work system concepts provide a basis for discussing and researching areas where behavioural science and computer science are jointly relevant to the operation and success of IT-reliant work systems through which organisations operate. This paper is organised as follows: it clarifies its view of ODE in general by proposing a general theory of ODE, that does not rely on work system concepts; it introduces basic ideas in the work system approach; it summarises a work system approach to ODE; it summarises three design spaces that are organised using work system concepts; it discusses correspondences and divergences with the original ODE white paper (Magalhaes and Silva, 2009); it summarises the advantages of a work system approach to ODE.